Analisis Kasus Pencucian Uang Rafael Alun Trisambodo dalam Hukum Administrasi Negara - Suryo, Angger Bagas; Putri, Audrey Rasya Novianto; Rahmadhana, Radya Alluna; Andi Fitra, Taufiqur Rahman; Tarina, Dwi Desi Yayi (Media Hukum Indonesia (MHI), 2024)
State administrative law is a branch of law that regulates the relationship between the government and the public, and regulates the mechanism for administrative decision-making by public officials. In this context, accountability and transparency are basic principles that must be upheld by government officials to maintain public trust. The case of Rafael Alun Trisambodo, an official at the Indonesian Ministry of Finance who was involved in alleged money laundering, has become a spotlight that highlights the challenges and dynamics in enforcing state administrative law. This study aims to explore the implications of state administrative law resulting from the case, with a focus on the role of regulation in preventing acts of corruption, as well as the importance of public oversight and participation. The methodology used is a qualitative analysis of legal documents, related policies, and media reports. The results of the study indicate that the implementation of stricter policies and proactive oversight are essential to strengthen public integrity and prevent the practice of abuse of power. These findings are expected to provide recommendations for the development of more effective state administrative law, as well as support the government's efforts to eradicate corruption in Indonesia.